Sharing-Knowledge Kekerasan Seksual Pada Remaja di PKBM Negeri 34 Cipayung - Raden Maisa Yudono; Hesti Rosdiana; Lia Wulandari (BERNAS: Jurnal Pengabdian Kepada Masyarakat, 2024)
Sexual violence is a crime that is in the spotlight of the world public, with adolescents as victims who are vulnerable to this crime. In Indonesia, sexual violence against adolescents is the highest case among other cases of violence. Lack of knowledge about sexual violence is one of the causes of high cases of sexual violence in adolescents in Indonesia. Therefore, briefing on sexual violence needs to be done to minimize sexual violence in adolescents. By carrying out 'Sharing-Knowledge of Sexual Violence in Adolescents', this community service activity aims to share knowledge and minimize sexual violence in adolescents, especially in the school environment. The method of lectures and watching films is the right choice in carrying out service activities. The result of this service activity is an increase in the understanding and awareness of adolescent students about sexual violence. In addition, the formation of the Task Force for the Prevention of Sexual Violence (STPTKS), is a concrete step that PKBM Negeri 34 students can take in the prevention and handling of sexual violence in adolescents, which can mainly be found in the school environment. Keywords: adolescent; sexual violence; sexual violence prevention Abstrak (Tahoma, 9pt Bold) Kekerasan seksual merupakan tindak kejahatan yang sedang menjadi sorotan publik dunia, dengan kaum remaja sebagai korban yang rentan akan tindak kejahatan ini. Di Indonesia, kekerasan seksual pada remaja merupakan kasus tertinggi diantara kasus kekerasan lainnya. Kurangnya pengetahuan tentang kekerasan seksual menjadi salah satu penyebab tingginya kasus kekerasan seksual pada remaja di Indonesia. Oleh karena itu, pembekalan tentang kekerasan seksual perlu dilakukan untuk meminimalisir kekerasan seksual pada remaja. Dengan melaksanakan ‘Sharing-Knowledge Kekerasan Seksual Pada Remaja’, kegiatan pengabdian kepada masyarakat ini bertujuan untuk berbagi ilmu dan meminimalisir tindak kekerasan seksual pada remaja, khususnya di lingkungan sekolah. Metode ceramah dan menonton film menjadi pilihan tepat dalam pelaksanaan kegiatan pengabdian. Hasil dari kegiatan pengabdian ini ialah meningkatnya pemahaman dan kesadaran siswa/i usia remaja akan tindak kekerasan seksual. Selain itu, terbentuknya Satuan Tugas Pencegahan Tindak Kekerasan Seksual (STPTKS), merupakan langkah nyata yang dapat dilakukan siswa/i PKBM Negeri 34 dalam pencegahan dan penanganan kekerasan seksual pada remaja, yang utamanya bisa saja ditemukan di lingkungan sekolah. Kata Kunci: remaja; kekerasan seksual; pencegahan kekerasan seksual